I—Living Causes. Issue 1 (4th June 2013) - Dupré, John
<x xml:space="preserve">Abstract</x> This paper considers the applicability of standard accounts of causation to living systems. In particular it examines critically the increasing tendency to equate causal explanation with the identification of a mechanism. A range of differences between living systems and paradigm mechanisms are identified and discussed. While in principle it might be possible to accommodate an account of mechanism to these features, the attempt to do so risks reducing the idea of a mechanism to vacuity. It is proposed that the solution to this problem requires the development of a philosophical account of process adequate to apply to living systems.